Thursday
March 23, 2017

Post a New Question

Posted by on Tuesday, March 6, 2012 at 12:19am.

Solve. Check for extraneous solutions.

1) (/3x+7) = x-1


2) (3/2x)-3=9




Note: (/3x+7) is the square root of 3x plus 7 and (3/2x)-3=9 is 3 times the square root of 2x - 3 equals 9.

  • math - , Tuesday, March 6, 2012 at 6:34am

    Thank you for clarifying your unconventional notation.

    1) sqrt(3x +7) = x-1
    3x + 7 = x^2 -2x + 1
    x^2 -5x -6 = 0
    (x-6)(x+1) = 0
    x = 6 or -1

    2. 3*sqrt(2x-3) = 9
    sqrt(2x -3) = 3
    2x -3 = 9
    x = 6

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question